Serum level of high mobility group box protein-1 and prognosis of patients with end-stage renal disease on hemodialysis and peritoneal dialysis. Issue 5 (5th February 2021) - Chen, Linyan; Chen, Gaoping; Kong, Xiangdong
Abstract : Abstract: To investigate serum level of high mobility group box protein-1 (HMGB1) and prognosis of patients with end-stage renal disease (ESRD) on hemodialysis (HD) and peritoneal dialysis (PD). This prospective cohort observational study included a total of 253 ESRD patients who came to our hospital for HD or PD from February 2013 to February 2015. Enzyme linked immunosorbent assay (ELISA) method was used to detect the serum level of HMGB1, interleukin (IL-6), IL-8, and tumor necrosis factor-alpha (TNF-α). The kidney disease quality of life short form (KDQOL-SF) and kidney disease targeted area (KDTA) was applied for evaluating the quality of life. Kaplan–Meier (K–M) curve was performed for survival time. Serum level of HMGB1 in patients on HD was higher than PD. HMGB1 levels were gradually decreased with the treatment of HD or PD. Furthermore, HMGB1 was positively correlated with IL-6 and TNF-α. Moreover, patients with higher HMGB1 had more complications than patients with lower HMGB1, but there was no difference for the survival rate. In addition, the quality of life was associated with different dialysis methods. The serum level of HMGB1 and prognosis of ESRD patients was associated with different dialysis methods.